1991
DOI: 10.1002/ange.19911031124
|View full text |Cite
|
Sign up to set email alerts
|

Heterotope Wirtmoleküle zur Einlagerung von zwei verschiedenen Gästen

Abstract: Wirtmoleküle mit Bor-haltigen Acceptor- und mit Kronenether-Donorstellen wie Verbindung 1 in der vorstehenden Zuschrift können selektiv Alkohole und Amine einlagern. Das Lewis-saure Bor-Zentrum greift in die Brønstedt-Eigenschaften des Systems Alkohol/Amin ein, so daß das Alkoholat am Bor- und das Ammonium-Ion am Kronenether-Teil gebunden ist. Die untenstehende Gleichung zeigt dies schematisch. Die Struktur der Wirt/Gast1/Gast2-Verbindungen ist äußerst ungewöhnlic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…For example, compound 136 is capable of coordinating to potassium and fluoride ions simultaneously. Reetz et al showed that the potassium ion is bound by the crown ether moiety present in this receptor whilst the fluoride ion is held by a combination of orbital overlap with the Lewis‐acidic boron atom and electrostatic interactions with the potassium ion 152, 153. The crystal structure of the potassium fluoride complex is shown in Figure 19.…”
Section: Into the New Millennium: Templation Anion‐directed Self‐mentioning
confidence: 99%
“…For example, compound 136 is capable of coordinating to potassium and fluoride ions simultaneously. Reetz et al showed that the potassium ion is bound by the crown ether moiety present in this receptor whilst the fluoride ion is held by a combination of orbital overlap with the Lewis‐acidic boron atom and electrostatic interactions with the potassium ion 152, 153. The crystal structure of the potassium fluoride complex is shown in Figure 19.…”
Section: Into the New Millennium: Templation Anion‐directed Self‐mentioning
confidence: 99%
“…Die Verbindung 136 koordiniert beispielsweise gleichzeitig Kalium‐ und Fluorid‐Ionen. Reetz et al fanden, dass das Kalium‐Ion von der Kronenethereinheit des Rezeptors gebunden wird, während das Fluorid‐Ion durch eine Kombination aus der Orbitalüberlappung mit dem Lewis‐sauren Boratom und der elektrostatischen Wechselwirkung mit dem Kalium‐Ion komplexiert wird 152, 153. Die Struktur des Kaliumfluorid‐Komplexes im Kristall ist in Abbildung 19 wiedergegeben.…”
Section: Auf Dem Weg Ins Neue Jahrtausend: Templatprozesse Anioneunclassified
“…However, molecular systems that can be used for simultaneous detection of cations and anions are rather limited. [37][38][39][40][41] It may be mentioned in this context that ditopic receptors are known to exhibit cooperative effects, where binding of one ion alters the binding affinity of the other. [39,42] The design of such systems is often governed by the complexity of the target molecular structure and therefore they are difficult to synthesize.…”
Section: Introductionmentioning
confidence: 99%